TNF-alpha gene polymorphisms in Iranian Azari Turkish patients with inflammatory bowel diseases - Mortaza Bonyadi; Reza Abdolmohammadi; Zohreh Jahanafrooz; Mohammad-Hosein Somy; Manoochehr Khoshbaten (The Saudi Journal of Gastroenterology, 2014)
Context: Crohn′s disease (CD) and ulcerative colitis (UC) are chronic inflammatory diseases of the bowel (IBD) whose causes are not fully known. Emerging data indicate that alterations in cytokine synthesis may play a role in IBD pathogenesis. Aims: We aimed to determine the association between tumor necrosis factor-alfa (TNFα) promoter polymorphisms (at positions − 308 and − 1031) and susceptibility to IBD among Iranian Azari Turkish patients. Settings and Design: One hundred and one patients with IBD and 100 healthy subjects were analyzed. Materials and Methods: Both polymorphisms in the promoter region of the TNFα gene at positions -1031T/C and -308G/A were detected by polymerase chain reaction-restriction fragment length polymorphism assay. All statistical analyses were calculated with SPSS for Windows 16.0. The Fisher′s exact test was used to test for departure from Hardy-Weinberg equilibrium of the genotype frequencies (P > 0.05). Results: The allele frequency of the TNFα-308G and -1031T were higher in IBD patients but did not reach statistical significance. However, the homozygous TT genotype for the SNP-1031 T > C was significantly higher in UC patients than in healthy controls (P = 0.01) and the heterozygous CT genotype for the SNP -1031 T > C was significantly lower in UC patients than in healthy controls (P = 0.03). Conclusions: The TNFα-1031 T allele confers a significant risk for developing UC in Iranian Azeri Turkish patients. Also the frequency of TNFα-1031 C allele was considerably low among patients with UC and it may have protective role among them (OR = 0.43; P = 0.01).